ANALYZING THE PATH OF RELIGIOUS RECONCILIATION IN PAKISTAN - Lvzi, Xu; Yan-E2, Yin (Journal of Social Science and Cultural, 2024)
This research article is a qualitative research article. The objectives are: 1. To research the causes of religious conflict in Pakistan through the study of historical data. 2. To research the possible paths of religious reconciliation in Pakistan from the causes of religious conflict. Islam in Pakistan continues to face threats from sectarian fighting. Religious and other sectarian extremism has had a serious impact on Pakistan's political and social stability. This is a qualitative research study based on document research. It is based on analysis and research of documents regarding Pakistan's religion, politics and forms of terrorism. Evolutionary development of Islam and the history of the Indian subcontinent to summarize the religious background of Pakistan. and the religious conflicts they face and aimed at finding ways to reconcile. The research results found that from the religious history of three important periods of the Mughal Empire. British India and the establishment of Pakistan. The struggle between Sunni and Shiite continues to be a key issue in Pakistan's sectarian struggle. It is also influenced by fundamentalist and collectivist Islam. Islam in Pakistan has become increasingly extremist. Later development and religious extremism have morphed into terrorism. It has become a major threat to peace. political stability and society of Pakistan to this day. Guidelines for building religious harmony are critical to Pakistan's security. In order to achieve religious harmony in Pakistan three aspects can be considered: historical integration at the national level; Understanding sects at the religious level and intellectual integration at the national level.